PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL KONTROL (STUDI PADA PERUSAHAAN PERTAMBANGAN DI BEI) - B11210111, Andryes (Universitas Tanjungpura, 2013)
The objective of this research are to identify empirical evidence about the effect of corporate governance component to the financial performance on mining companies. The sample in this study is mining company that has listed in Bursa Efek Indonesia (BEI) during the period from 2009 to 2011. The result showed that the component of corporate govenance have a significant effect on firm value as measured by TobinsQ, while the companys performance as measured by ROE the effect becomes insignificant. Also from GCG component, only board of the directors, have a significant influence on financial perfomance by using TobinsQ showed a significant positive effect. The suggestion in this research is corporate governance mechanisms need to be implemented by the mining company not only as a formality to complete the legality of the company, but use it as a monitoring function for the company in an effort to improve financial performance. Keywords: Good Corporate Governance Component, ROE, TobinsQ